2012
DOI: 10.1039/c2ob25647a
|View full text |Cite
|
Sign up to set email alerts
|

7-Substituted 8-aza-7-deazaadenosines for modification of the siRNA major groove

Abstract: Here we describe the synthesis of new 7-substituted 8-aza-7-deazaadenosine ribonucleoside phosphoramidites and their use in generating major groove-modified duplex RNAs. A 7-ethynyl analog leads to further structural diversification of the RNA via post-automated RNA synthesis azide/alkyne cycloaddition reactions. In addition, we report preliminary studies on the effects of eight different purine 7-position modifications on RNA duplex stability and pairing specificity. Finally, the effect on RNAi activty of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…4,16 A fraction of the 7-EAA-containing RNA was then subjected to a CuAAC reaction with N -ethylpiperidine azide to give a 16 nt RNA bearing the N -ethylpiperidine 7-EAA triazole (Figure 3A). After purification by polyacrylamide gel electrophoresis, 16 nt RNAs bearing 7-EAA, 7-EAA triazole, and adenosine (for comparison) were crystallized.…”
Section: Resultsmentioning
confidence: 99%
“…4,16 A fraction of the 7-EAA-containing RNA was then subjected to a CuAAC reaction with N -ethylpiperidine azide to give a 16 nt RNA bearing the N -ethylpiperidine 7-EAA triazole (Figure 3A). After purification by polyacrylamide gel electrophoresis, 16 nt RNAs bearing 7-EAA, 7-EAA triazole, and adenosine (for comparison) were crystallized.…”
Section: Resultsmentioning
confidence: 99%
“…363 The modification is accomplished at the 7-position of purine, since this site is not directly involved in Watson Crick base-pairing. 364 The click reactions in cells occur in very limited area so that the location of biomaterials in cells can be analyzed with nanometer resolution by use of electron microscopy. Tsien et al devised elegant systems in which DNA, RNA and lipids in cultured cells and neurons can be labelled and clearly distinguished on electron microscopy from the other molecules in cells (Figure 21).…”
Section: Selectivementioning
confidence: 99%
“…19,[24][25][26][27][28][29] In particular, 7-deazapurines, as well as 7-deaza-8-azapurine analogues have been reported to be suitable for modification by copper-catalyzed azide/alkyne cycloaddition (CuAAC or click) chemistry, and used to modify siRNA molecules and to probe RNA editing by adenosine deaminases. 18,19,30,31 This explains why several efforts have been aimed at the synthesis of different purine analogues including 7-deaza-8-azapurine and its 7-substituted derivatives. In particular, Beal's group focused on exploring modifications of nucleic acid residues that project different substituents either in the minor groove (the sugar edge) or in the major groove (the Hoogsteen edge) of a siRNA duplex.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Beal's group focused on exploring modifications of nucleic acid residues that project different substituents either in the minor groove (the sugar edge) or in the major groove (the Hoogsteen edge) of a siRNA duplex. 19,30,31 Indeed, the synthesis of nucleobase analogues that retains the 'Watson-Crick' like pairing and that place the substituent in the major-groove is of particular interest, since they preserve the duplex stability and do not alter recognition by the nuclease of the RNA interference (RNAi) pathway. 31 In this context, a very recent study 31 reported the impact on RNA duplexes of two modifications located on the major groove (the "Hoogsteen edge") of the adenine moiety, namely 7-ethynyl-7-deaza-8-aza adenine (here-on 7-E-7-DAA) and 7-triazole-7-deaza-8-azaadenine (7-T-7-DAA),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation